The impact of instructional media and cultural intelligence on maritime English literacy: A meta-analysis - Aliya Izet Begovic Yahya; Merry Lapasau; Syahfitri Purnama; Oom Rohmah Syamsudin; Abdulkarimu Yanda (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2025)
This study aims to analyze the influence of learning media and cultural intelligence on Maritime English literacy through a quantitative meta-analysis approach. A total of 28 journal articles published between 2012 and 2025 were systematically reviewed based on the PRISMA protocol, involving a combined sample of 3,164 participants from various educational levels and maritime training institutions. Statistical synthesis was conducted using JASP software to obtain pooled effect sizes and assess heterogeneity across studies. The results revealed that both variables had a positive and significant impact on Maritime English literacy. Learning media demonstrated a strong effect size of 0.782 (p < 0.001) with high heterogeneity (I² = 89.59%), reflecting diverse contexts of media implementation. Cultural intelligence showed a moderate effect size of 0.523 (p < 0.001) with very high heterogeneity (I² = 96.99%), indicating contextual variations across studies. These findings affirm that digital and interactive media, as well as cross-cultural competence, play a vital role in enhancing maritime learners’ English proficiency and global communication readiness. The study contributes to both theory and practice by providing a comprehensive quantitative synthesis of the determinants of Maritime English literacy. The results offer a strong empirical foundation for developing technology-based and culturally responsive teaching strategies, aligned with the Standards of Training, Certification, and Watchkeeping for Seafarers (STCW) and International Maritime Organization (IMO) standards.